2006
DOI: 10.3758/bf03194016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of return lasts longer at repeatedly stimulated locations than at novel locations

Abstract: Inhibition of return (IOR) refers to the fact that it takes longer for people to attend to recently examined locations than to novel locations. It has been argued that a single mechanism governs both IOR and negative priming (NP). If this is true, IOR and NP should share similar characteristics. Since NP depends on the use of repeated stimuli, in this study the dependence of IOR on repeated stimuli was explored. Experiments 1A-1D showed that, at longer cue-to-target-onset asynchrony (CTOA) intervals (613 and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The results of the current study provided further evidence indicating that IOR and location NP may share a common mechanism (Buckolz, Boulougouris, O’Donnell, & Pratt, 2002; Chao & Yeh, 2006; Christie & Klein, 2001; Milliken, Tipper, Houghton, & Lupiáñez, 2000). The procedure of Experiment 1 was similar to most IOR studies wherein a nonmeaningful cue (e.g., a box cue) was used to capture attention, while the procedure of Experiment 2 was similar to a single-prime NP task.…”
Section: Discussionsupporting
confidence: 76%
“…The results of the current study provided further evidence indicating that IOR and location NP may share a common mechanism (Buckolz, Boulougouris, O’Donnell, & Pratt, 2002; Chao & Yeh, 2006; Christie & Klein, 2001; Milliken, Tipper, Houghton, & Lupiáñez, 2000). The procedure of Experiment 1 was similar to most IOR studies wherein a nonmeaningful cue (e.g., a box cue) was used to capture attention, while the procedure of Experiment 2 was similar to a single-prime NP task.…”
Section: Discussionsupporting
confidence: 76%
“…In other domains, contextual repetition enables inhibition of return (Chao and Yeh, 2006), that is, avoiding attending to something to which one previously attended. Here, contextual repetition likely enabled children to allocate less attention to the plots, characters and scenes as well as more attention to the novel name–object pairs each time the same story was repeated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that IOR and the repetition costs in the location-selection paradigm may reflect the operation of the same mechanism (Christie & Klein, 2001, 2008; Milliken et al, 2000). Consistent with this hypothesis, it has been demonstrated that both IOR and location NP are contingent on location repetition (Chao & Yeh, 2005, 2006). In addition, Buckolz, Boulougouris, O'Donnell, and Pratt (2002) demonstrated that when there was a 100% valid precue of the target location, the location NP effect was reduced.…”
mentioning
confidence: 57%
“…Hence, it is tentatively concluded that location NP and IOR involve different mechanisms. However, in light of the similarities between these two phenomena (e.g., Buckolz et al, 2002; Chao & Yeh, 2005, 2006), further studies are required to clarify their relationship.…”
Section: Discussionmentioning
confidence: 99%